Geological reconnaissance of the Sör-Rondane mountains (Queen Maud Land) - Picciotto, Edgardo (1960)
IN the course of the summer field parties of the Expedition Antarctique Beige 1957-58, I carried out a geological reconnaissance in the Sör-Rondane ranges, unexplored up to then. © 1960 Nature Publishing Group. SCOPUS: ar.j info:eu-repo/semantics/published